2008
DOI: 10.1016/j.jasms.2007.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Regioselectivity of human UDP-glucuronosyl-transferase 1A1 in the synthesis of flavonoid glucuronides determined by metal complexation and tandem mass spectrometry

Abstract: A three-part tandem mass spectrometric strategy that entails MS n analysis and a post-column LC-MS cobalt complexation method is developed to identify flavonoid monoglucuronide metabolites synthesized using the 1A1 isozyme of human UDP-glucuronosyltransferase (UGT). Ten flavonoid aglycons were used as substrates, spanning the subclasses of flavones, flavonols, and flavanones. The products were characterized by LC-MS and LC-MS n , with post-column cobalt complexation employed to pinpoint the specific sites of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(77 citation statements)
references
References 56 publications
3
72
2
Order By: Relevance
“…It has been reported that 7-O-glucuronide was eluted prior to the elution of 4 -O-glucuronide during analysis by reversed-phase high performance liquid chromatography (HPLC) on a C18 or C8 column [15][16][17]. Our experiments demonstrated that the retention times for M1 and M2 were 3.9 and 5.0 min, respectively.…”
Section: Metabolites Of Puerarin In Rat Plasmamentioning
confidence: 62%
See 1 more Smart Citation
“…It has been reported that 7-O-glucuronide was eluted prior to the elution of 4 -O-glucuronide during analysis by reversed-phase high performance liquid chromatography (HPLC) on a C18 or C8 column [15][16][17]. Our experiments demonstrated that the retention times for M1 and M2 were 3.9 and 5.0 min, respectively.…”
Section: Metabolites Of Puerarin In Rat Plasmamentioning
confidence: 62%
“…It has been reported that different conjugation sites of the glucuronide group results in different retention behaviors in HPLC analysis [15][16][17]. An elution rule was reported when separation of flavonoid monoglucuronide isomers was performed by reversed-phase HPLC, that is, the 4 -glucuronide isoflavones were retained for longer than their 7-isomers [15][16][17], regardless of the exact chromatographic method employed. In our experiments, the retention times for M1 and M2 were 3.9 and 5.0 min, respectively, so that presumably, M1 is puerarin-7-O-glucuronide and M2 is puerarin-4 -O-glucuronide.…”
Section: Discussionmentioning
confidence: 99%
“…This ability to chelate metals has been used to enhance the capabilities of MS; it has been used to assist the elucidation of flavonoid glucuronides (Davis et al, 2006;Davis et al, 2007) and various diglycosides (Pikulski et al, 2007). This is a result of the spectral changes observed when flavonoids are complexed with metals, giving rise to simpler yet more intense spectra (Satterfield & Brodbelt, 2000).…”
Section: Fig 1 Binding Sites For Trace Metals Where Men+ Indicates mentioning
confidence: 99%
“…Previous studies reported that the Caco-2 cell model has the ability to digest Tween 80 in the absence of pancreatin to liberate oleic acid, which was then used by the cells to enhance the basolateral secretion of chylomicrons 31 . Further, co-administration of olive oil and Tween 80 increased the formation of chylomicrons in the rat 32 and quercetin was transported into lymph after being metabolised in the gastrointestinal mucosa of rats 33,34 . In humans, a suspension in pure soybean oil increased the bioavailability of coenzyme Q10 compared to lipid formulations that included Tween 80 and/or phosphatidylcholine as surfactant.…”
Section: Discussionmentioning
confidence: 95%